Epidemiology and molecular characterization of Porcine teschovirus in Hunan, China. Issue 2 (16th October 2017) - Yang, T.; Yu, X.; Luo, B.; Yan, M.; Li, R.; Qu, T.; Ren, X.
Summary: Porcine teschoviruses (PTVs) have been shown to be widely distributed in pig populations. In this study, 261 faecal and 91 intestinal content samples collected from pigs at 29 farms in Hunan, China, were tested for the presence of PTV by reverse transcription‐polymerase chain reaction (RT‐PCR). An overall PTV‐positivity rate of 19.03% was detected by RT‐PCR, and a high PTV infection rate was circulating in asymptomatic fattening and nursery pigs. In total, 40 PTV isolates (PTV‐HuNs) were obtained. Alignment of their coding sequences with those of other known PTVs revealed that the genomic sequence of the polyprotein contains 6, 606–6, 621 nucleotides, encoding a 2, 202–2, 207‐amino acid sequence. Phylogenetic analyses based on the VP1 gene and capsid protein gene exhibited 13 main lineages corresponding to PTV serotypes 1–13, and seven PTV serotypes (PTV 2–6, 9, and 11) were identified in the isolates obtained in our study; this is the first report of PTV 5, 9 and 11 in China. Recombination analysis among the PTV‐HuNs indicated that nine recombination events have occurred, including both inter‐ and intraserotype events. In addition, results demonstrated that only limited positive selection is acting on the global population of PTV isolates, and purifying selection is predominant. In conclusion, this study revealed a high infection rate of PTVs circulating in asymptomatic fattening and nursery pigs. The 40 PTV‐HuNs showed high genetic diversity, and genetic analysis of all available PTV sequences revealed that strong purifying selection and recombination play important roles in the genetic diversity and evolution of the virus.